PENGARUH ORIENTASI PASAR, PERILAKU KEWIRAUSAHAAN, DAN MOTIVASI TERHADAP KINERJA BISNIS PADA SENTRA UKM ( STUDI KAMPUNG KUE KEC. RUNGKUT KOTA SURABAYA ) - Jannah, Septika Atul (Research Journal of Social Science and Economics, 2025)
This study aims to determine: (1) The effect of market orientation on business performance in UKM Kampung Kue Kec. Rungkut Surabaya City, (2) The Effect of Entrepreneurial Behavior on Business Performance in Kampung Kue Kec. Rungkut Surabaya City, (3) The Influence of Motivation on Business Performance in Kampung Kue Kec. Rungkut City of Surabaya,. This research was conducted at Kampung Kue Kec. Rungkut Surabaya City, This research includes associative research or relationships using a quantitative approach. The population in this study were all cake village business owners in the district. Rungkut city of Surabaya. Sampling technique with certain considerations with a total sample of 44 people. The data collection technique uses a questionnaire that has been tested for validity and reliability, and the data analysis technique used is the classical assumption test, multiple linear regression. The results showed that (1) there was a positive effect of market orientation on business performance in Kampung Kue Kec. Rungkut, Surabaya City, is proven by the t-test value for the market orientation variable, namely a significance value of 0.049 is less than 0.05 (0.049 <0.05). (2) there is a positive influence of entrepreneurial behavior on business performance in Kampung Kue Kec. Rungkut, Surabaya City, is proven by the t test value for the entrepreneurial behavior variable, namely a significance value of 0.001 is less than 0.05 (0.001 <0.05). (3) there is a positive influence of motivation on business performance in Kampung Kue Kec. Rungkut Surabaya City, proven by the t test value for the entrepreneurial behavior variable, namely a significance value of 0.008 is less than 0.05 (0.008 < 0.05).